Ni Nanoparticles on Reducible Metal Oxides (Sm2O3, CeO2, ZnO) as Catalysts for CO2 Methanation - Athirah Ayub; Hasliza Bahruji; Abdul Hanif Mahadi (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
The activity of reducible metal oxide Sm2O3, CeO2, and ZnO as Ni nanoparticles support was investigated for CO2 methanation reaction. CO2 methanation was carried out between 200 °C to 450 °C with the optimum catalytic activity was observed at 450 °C. The reducibility of the catalysts has been comparatively studied using H2-Temperature Reduction Temperature (TPR) method. The H2-TPR analysis also elucidated the formation of surface oxygen vacancies at temperature above 600 °C for 5Ni/Sm2O3 and 5Ni/CeO2. The Sm2O3 showed superior activity than CeO2 presumably due to the transition of the crystalline phases under reducing environment. However, the formation of NiZn alloy in 5Ni/ZnO reduced the ability of Ni to catalyze methanation reaction. A highly dispersed Ni on Sm2O3 created a large metal/support interfacial interaction to give 69% of CO2 conversion with 100% selectivity at 450 °C. The 5Ni/Sm2O3 exhibited superior catalytic performances with an apparent phase transition from cubic to a mixture of cubic and monoclinic phases over a long reaction, presumably responsible for the enhanced conversion after 10 h of reaction. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).